Optimizing Problem-Based Learning on Salt Hydrolysis Material for Critical Thinking and Student Learning Activities - Islawati; Cahyani, Vika Puji; Fadly, Dewiyanti; Ahmad, Fandi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This research aims to evaluate the effect of applying the Problem-Based Learning (PBL) Learning Model on students' critical thinking abilities and learning activities in studying salt hydrolysis material. The research method used was a quasi-experiment using two groups: an experimental group that applied PBL and a control group that used conventional learning methods. The research sample consisted of class XI students at a high school in an urban area. Data was collected through critical thinking ability tests before and after treatment, as well as observations of students' learning activities during the learning process. The results of data analysis show that there is a significant increase in the critical thinking skills and learning activities of students who take part in learning using the PBL model compared to the control group. Students in the PBL group showed a higher level of involvement in group discussions, problem solving, and searching for additional information related to salt hydrolysis material. The implication of this research is that PBL can be an effective approach in improving the quality of chemistry learning at the high school level, especially in strengthening critical thinking skills and increasing students' learning activities. Pre-test scores revealed no significant differences between the control group and the treatment group in terms of critical thinking skills (p > 0.05). However, post-test scores demonstrated a substantial increase in critical thinking skills among students in the treatment group (M = 85.6, SD = 7.2) compared to those in the control group (M = 72.3, SD = 6.8), with a statistically significant difference (p < 0.001). Therefore, it is recommended that PBL be applied more often in the context of chemistry learning to optimize student learning outcomes.